Building Organizational Culture in Islamic Education with Collaborative Leadership as the Key - Afkarina, Miftahul; Puspita W, Dhevin MQ Agus (AFKARINA: Jurnal Pendidikan Agama Islam, 2023)
This study aims to identify and describe the main dimensions of collaborative leadership that are relevant in the context of Islamic education. The background of this study is rooted in the assumption that a leader must be able to be an effective leader, with the same goal of providing guidance, setting an example, and directing members to improve while helping to solve organizational problems. In this study, the method used is qualitative research through literature study, which examines and synthesizes findings from research and theories that exist in previous scientific works. The findings indicate that collaborative leadership is a viable option for developing an Islamic education culture. With the increasing diversity of Islamic education in Indonesia, the leadership style applied must be integrated with Islamic values. As a creature of Allah SWT who maximizes the ability to allocate efforts in educational institutions, instilling Islamic character is very important and can be achieved through the implementation of daily behavior, which will ultimately shape the organizational culture. This study contributes to the understanding that the application of collaborative leadership in Islamic education has great potential to improve the quality of education and create a more inclusive and meaningful learning environment, with Islamic values such as ta'awun (mutual assistance), shura (deliberation), and ukhuwah (brotherhood) that support the principles of collaborative leadership.